Suppply chain analysis of Indonesia tea - Suprihatini, Rohayati (Research Institute for Tea and Cinchona, 2015)
Indonesian tea market share tend to decrease due to the weakness of competitive advantage of Indonesian tea. The weakness of Indonesian tea competitiveness should be cla-rified by supply chain. Primary data collected from survey as well as expert meeting. Analysis method applied in this research is supply chain analysis. Research results showed that in term of Indonesia tea production of 165.070 tons in 2006, tea volume to be processed to down-stream products for domestic consumption is around 62.776 tons. The rest is for export pur-poses consists of bulk black tea export (92.763 tons) as well as bulk green tea export (9.531Â tons). This condition relatively stable up to 2013 due to Indonesia tea import volume around 20,000 ton disburse to domestic con-sumption (55%) as well as re-export purposes (45%). The most of smallholder tea production (63%) come to jasmine tea processors located in Central Java. Farm gate price of green leaf is around 15,8% of consumer price of jasmine tea. Total margin of supply chain from tea farmers to jasmine tea consumers is around Rp22.100,00/kg of made tea consists of Rp13.121,00/kg made tea (50% of total margin) as cost margin and Rp8.979,00/kg made tea (34,1%) as profit margin. To remedy supply chain of smallholder tea should remedy factors affecting supply chain. Priority factors should be improved i.e. (1) quality of tea in each chain, (2) availability as well as assistancy to credit access, and (3) conducive of trade policies.